Gender Differences in Growth in Mathematical Skills During Secondary Grades: A Growth Model Analysis - Ma, Xin (Alberta Journal of Educational Research, 1999)
The purpose of this study was to examine differences in the rate at which males and females acquired mathematical skills during secondary grades and to determine the relationship between their rates of growth and student- arid school-level characteristics. Based on data from the Longitudinal Study of American Youth (LSAY), a three-level hierarchical linear model (HLM) indicated that males and females acquired mathematical skills at the same rate. The variation in scores among students increased over time, and students maintained their initial position in the distribution. This fan-spread phenomenon among students was more pronounced in basic skills and knowledge than in problem-solving. Schools were more homogeneous in female rate of growth than in male rate of growth. The variation in scores among schools enlarged over time, and schools maintained their initial position in the distribution. This fan-spread phenomenon among schools was more pronounced in basic skills and knowledge than in problem-solving. Policy implications and suggestions for future research are provided.